Plantas espontâneas em cultivos de couve estratégia para aumento da diversidade da entomofauna e regulação de pulgões - Santos, Adriano Jorge Nunes dos (2015)
Organic crop systems needs sustainable strategies for pest management, which can be obtained by environmental manipulation, using weeds, which are able to provide important resources for natural enemies conservation. The objective of this study was to evaluate the role of presence, weeding range and composition of spontaneous plants as a strategy for conservation of arthropod diversity and regulation of aphid infestation in cabbage crop. For this, we developed three field experiments in horticultural production area of the Department of Agriculture of the Federal University of Lavras - UFLA, Lavras, Minas Gerais. The first assessed the contribution of the community of spontaneous plants in cabbage and tomato crops in relation to diversity and abundance of arthropods and pest regulation. The second studied the influence of different weeding intervals of spontaneous vegetation on the populations of parasitoids, predators, and two species of aphids of brassica. The third looked at the effect of the composition of spontaneous plant species on the infestation of aphids and populations of aphidophagous natural enemies in cabbage crop. Weeds had a positive effect on maintenance and conservation of the diversity of arthropods in cabbage crop. Lower aphid infestations were found in the weed presence, less frequent weeding and greater diversity of spontaneous plants. Predators and parasitoids abundance were higher in plants with higher pest infestation. Thus, the maintenance of weeds is recommended as a strategy for aphid control in organic cabbage crop.